Islamic Community Development: Perspective, Science and Practice - Tandos, Rosita (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2025)
In the field of Islamic studies and social work, community development is one of studies that have philosophical and practical bases, emphasizing Islamic values, research and action. In addition, it focuses on community and organizational works. This article provided an analysis of Islamic community development’s dimensions including history, principles, body of knowledge and models for empowerment. Recently, it becomes far more important in responding current issues and challenges besides opportunities, and its intersectionality with others issues and interconnectivity with other disciplines of studies. The last point that this study highlighted was the implementation of Islamic community development (ICD) studies at Islamic Higher Education of Ministry of Religious Affairs of the Republic of Indonesia, the reflection of ICD practices in one of faith-based organizations (FBOs) of Great Mosque of Istiqlal in Jakarta city.